Analisis Social Influence, Perceived Ease of Use terhadap Behavioural Intention dengan Mediasi Perceived Usefulness - Lily Purwianti; Maggie Maggie (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2024)
The emergence of Covid-19 pandemic has spread widely to various countries, which of one includes Indonesia. Where in 2020, Indonesia also impact on this pandemic, so the government took action on PPKM policy regulations by recommending all activities carried outside such as work, carried out at home to reduce circulation wider spread of the virus. After going through a situation where people must comply with health protocols and maintain cleanliness. Where at the end of 2022, the Ministry of Health announced that active cases of Covid-19 had decreased consistently and gave optimism to the current efforts to deal with Covid-19, of course it has made people accumulate an extraordinary willingness to travel. Due to the emergence of people's behavioral intentions to travel by ordering their travel activities on online booking service provider applications, where these applications can provide convenience and useful for them so that does not require excessive effort also can be used easily and efficiently. Indirectly it can also make the tourism industry continue to experience the most significant growth in searching for online travel agents because people's behavioral intentions are influenced by social influences that can provide convenience and benefits when using online booking service provider applications.